2000
DOI: 10.12968/bjcn.2000.5.3.7423
|View full text |Cite
|
Sign up to set email alerts
|

A review of the psychosocial aspects of multiple sclerosis

Abstract: The psychosocial aspects of multiple sclerosis are far-reaching and may have devastating effects on individuals and carers alike. Issues such as the impact of uncertainty, the need to maintain hope and control, and a person's ability to adjust his/her lifestyle to the disease progression are highlighted by recent research. The individualized nature of this chronic illness experience makes comprehensive and ongoing assessment crucial. Evidence from practice suggests that the district nurse's contribution to psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Knowledge about disease Miller (1997), Robinson et al (1996), Somerset et al (2001), Williamson (2000), Campion (1996aCampion ( , 1996b, Robinson (1991) 3 1 2 6…”
Section: Hypotheses I and Iimentioning
confidence: 99%
“…Knowledge about disease Miller (1997), Robinson et al (1996), Somerset et al (2001), Williamson (2000), Campion (1996aCampion ( , 1996b, Robinson (1991) 3 1 2 6…”
Section: Hypotheses I and Iimentioning
confidence: 99%
“…Furthermore, often the attitude towards, and acceptance of, other support on the part of the primary caregiver, usually a close family relation, will change over time [12]. Social and family support has consistently appeared throughout the literature on rehabilitation and adjustment to disability [13] and has been identified a salient factor in an individual's adjustment to MS [9,11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the difficulty of predicting fatigue (in other words, its uncertainty) made social interaction difficult. The uncertainty that is related to the possible recurrence of MS and the uncertainty of treatment results have been reported by many researchers (Miller, 1997; Williamson, 2000). Many investigators have reported that patients' lives are shaken by relapses and the instability of treatment effects.…”
Section: Discussionmentioning
confidence: 99%